DETEKSI KEBERADAAN Phytophthora spp. DI AIR - Purnamila Sulistyawati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2014)
The genus of Phytophthora is a destructive plants pathogen. However the existence of these species in plant tissue was hardly to detect because the fungus may also be present as resistant propagules in soil or spread through waterways. This study aimed to test the FTA card as a direct bait to obtain the DNA of Phytophthora spp and also to investigate the suitability of FTA card as a sampling method. This research used several Phytophthora baits including FTA card followed by DNA extraction and PCR used ITS primers and genus/species specific primers. The result of the study showed that FTA card can be used as a direct bait for Phytophthora spp. and to sample fungal DNA from other Phytophthora baits. However, further optimisation and validation are still required.